Uses of Laccases in the Food Industry. (1st September 2010) - Osma, Johann F.; Toca-Herrera, José L.; Rodríguez-Couto, Susana
Abstract : Laccases are an interesting group of multi copper enzymes, which have received much attention of researchers in the last decades due to their ability to oxidise both phenolic and nonphenolic lignin-related compounds as well as highly recalcitrant environmental pollutants. This makes these biocatalysts very useful for their application in several biotechnological processes, including the food industry. Thus, laccases hold great potential as food additives in food and beverage processing. Being energy-saving and biodegradable, laccase-based biocatalysts fit well with the development of highly efficient, sustainable, and eco-friendly industries.